Hepatitis B virus and hepatitis D virus infection in women with or at risk for HIV infection in the United States - Argirion, Ilona; Mahale, Parag; Pfeiffer, Ruth M.; Liu, Ping; Adimora, Adaora A.; Akiyama, Matthew J.; Bolivar, Hector H.; French, Audrey; Plankey, Michael; Price, Jennifer C.; Rana, Aadia; Sheth, Anandi; et al. (Frontiers in Medicine, 2023)
Hepatitis D virus (HDV) requires co-infection with hepatitis B virus (HBV). Human immunodeficiency virus (HIV) shares transmission routes with these viruses. Among 4932 US women infected with or at-risk for HIV during 1994-2015, HBV surface antigen (HBsAg) positivity was more common in women with HIV (2.8% vs 1.2%; p=0.001); HDV was more common among participants enrolled during 2013-2015 (p=0.0004) and those with resolved rather than active hepatitis C (1.9% vs 0.5%; p=0.02). Among HBsAg-positive women (n=117), HDV antibody prevalence was 22% and did not vary by HIV status; HDV infection was associated with the presence of advanced fibrosis/cirrhosis at enrollment (adjusted odds ratio, 5.70; 95% confidence interval, 1.46-22.29). Our results demonstrate the importance of HDV testing in HBV-infected US women.